Homologous Strategy to Construct High-Performance Coupling Electrodes for Advanced Potassium-Ion Hybrid Capacitors - Xu, Ying; Ruan, Jiafeng; Pang, Yuepeng; Sun, Hao; Liang, Chu; Li, Haiwen; Yang, Junhe; Zheng, Shiyou (Nano-Micro Letters, 2020)
Potassium-ion hybrid capacitors (PIHCs) have been considered as promising potentials in mid- to large-scale storage system applications owing to their high energy and power density. However, the process involving the intercalation of K+ into the carbonaceous anode is a sluggish reaction, while the adsorption of anions onto the cathode surface is relatively faster, resulting in an inability to exploit the advantage of high energy. To achieve a high-performance PIHC, it is critical to promote the K+ insertion/desertion in anodic materials and design suitable cathodic materials matching the anodes. In this study, we propose a facile “homologous strategy” to construct suitable anode and cathode for high-performance PIHCs, that is, unique multichannel carbon fiber (MCCF)-based anode and cathode materials are firstly prepared by electrospinning, and then followed by sulfur doping and KOH activation treatment, respectively. Owing to a multichannel structure with a large interlayer spacing for introducing S in the sulfur-doped multichannel carbon fiber (S-MCCF) composite, it presents high capacity, super rate capability, and long cycle stability as an anode in potassium-ion cells. The cathode composite of activated multichannel carbon fiber (aMCCF) has a considerably high specific surface area of 1445 m2 g−1 and exhibits outstanding capacitive performance. In particular, benefiting from advantages of the fabricated S-MCCF anode and aMCCF cathode by homologous strategy, PIHCs assembled with the unique MCCF-based anode and cathode show outstanding electrochemical performance, which can deliver high energy and power densities (100 Wh kg−1 at 200 W kg−1, and 58.3 Wh kg−1 at 10,000 W kg−1) and simultaneously exhibit superior cycling stability (90% capacity retention over 7000 cycles at 1.0 A g−1). The excellent electrochemical performance of the MCCF-based composites for PIHC electrodes combined with their simple construction renders such materials attractive for further in-depth investigations of alkali-ion battery and capacitor applications. Highlights: 1 A novel and facile homologous strategy is proposed to construct unique multichannel carbon fiber (MCCF)-based electrode materials for potassium-ion hybrid capacitors. 2 The S-MCCF anodes present high capacity, super rate capability, and long cycle stability in potassium-ion half-cells, and the aMCCF cathodes have a high specific surface area of 1445 m2 g−1 and exhibit outstanding capacitive performance. 3 The fabricated PIHC (manode:mcathode = 1:2) devices show high energy and power densities together with excellent cycling stability.